Comparative treatment planning study for mediastinal Hodgkin's lymphoma: impact on normal tissue dose using deep inspiration breath hold proton and photon therapy. (2nd January 2019) - Edvardsson, Anneli; Kügele, Malin; Alkner, Sara; Enmark, Marika; Nilsson, Joakim; Kristensen, Ingrid; Kjellén, Elisabeth; Engelholm, Silke; Ceberg, Sofie
Abstract: Background: Late effects induced by radiotherapy (RT) are of great concern for mediastinal Hodgkin's lymphoma (HL) patients and it is therefore important to reduce normal tissue dose. The aim of this study was to investigate the impact on the normal tissue dose and target coverage, using various combinations of intensity modulated proton therapy (IMPT), volumetric modulated arc therapy (VMAT) and 3-dimensional conformal RT (3D-CRT), planned in both deep inspiration breath hold (DIBH) and free breathing (FB). Material and methods: Eighteen patients were enrolled in this study and planned with involved site RT. Two computed tomography images were acquired for each patient, one during DIBH and one during FB. Six treatment plans were created for each patient; 3D-CRT in FB, 3D-CRT in DIBH, VMAT in FB, VMAT in DIBH, IMPT in FB and IMPT in DIBH. Dosimetric impact on the heart, left anterior descending (LAD) coronary artery, lungs, female breasts, target coverage, and also conformity index and integral dose (ID), was compared between the different treatment techniques. Results: The use of DIBH significantly reduced the lung dose for all three treatment techniques, however, no significant difference in the dose to the female breasts was observed. Regarding the heart and LAD doses, large individual variations were observed. For VMAT, the mean heart and LAD doses were significantly reduced using DIBH, but no significant difference was observed for 3D-CRT and IMPT. Both IMPT and VMAT resulted in improved target coverage and more conform dose distributions compared to 3D-CRT. IMPT generally showed the lowest organs at risk (OAR) doses and significantly reduced the ID compared to both 3D-CRT and VMAT. Conclusions: The majority of patients benefited from treatment in DIBH, however, the impact on the normal tissue dose was highly individual and therefore comparative treatment planning is encouraged. The lowest OAR doses were generally observed for IMPT in combination with DIBH.